2004
DOI: 10.1002/pds.963
|View full text |Cite
|
Sign up to set email alerts
|

Use and adherence to beta‐blockers for secondary prevention of myocardial infarction: who is not getting the treatment?

Abstract: Beta-blocker use was lower in older patients, patients with airways disease, PVD and heart failure, but these patients appeared to have the greatest benefit from beta-blockers. Good adherence to beta-blocker treatment after MI was associated with a lower risk of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 30 publications
6
40
1
Order By: Relevance
“…A few studies extend their follow-up to 1 year. 7,9,10,21,22 Yet, in our study population, there is no sign of leveling in the discontinuation rates after 1 year post-AMI. We identified two studies examining adherence beyond the first year post-AMI, 8,11 which have limited generalizability, and more importantly, examine Figure 2.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…A few studies extend their follow-up to 1 year. 7,9,10,21,22 Yet, in our study population, there is no sign of leveling in the discontinuation rates after 1 year post-AMI. We identified two studies examining adherence beyond the first year post-AMI, 8,11 which have limited generalizability, and more importantly, examine Figure 2.…”
Section: Discussioncontrasting
confidence: 58%
“…4 Limited data suggest that many patients who initiated these regimes after AMI have low rates of longterm persistence. [7][8][9][10] Beta-blocker or ACEI therapies are indicated for other diseases (e.g., coronary artery disease and hypertension), and studies following patients with such conditions also demonstrated low long-term adherence rates. [10][11][12][13][14][15] To identify subpopulations at greatest risk of therapy discontinuation, this study used administrative data from a large U.S. health plan to describe patient characteristics and comorbidities associated with increased rates of therapy discontinuation during the 2 years after AMI.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison with other studies is not straightforward; the literature on sex-based disparities in adherence to cardiovascular drugs is mixed and results vary by drug class; some studies show that women have better adherence to angiotensin-converting enzyme inhibitor/angiotensin receptor blockers and BBs 31 or statins, 32 whereas others reveal that men have better adherence to statins, [33][34][35][36] BBs, 31,37 and aspirin. 34,38 This between-study variation may be partially attributable to the structure of the healthcare system and drug reimbursement, differences in prescribing practices across jurisdictions, and differences in adherence measurement.…”
Section: Adherence To Pharmacotherapymentioning
confidence: 99%
“…However, post-AMI beta-blocker therapy is often underutilized [6][7][8][9][10]. Only 61% of patients who were candidates for post-AMI beta-blocker therapy actually initiated it in British Columbia, Canada, between 2001 and 2004 [9].…”
Section: Introductionmentioning
confidence: 99%